Job Satisfaction Determinants and Its Impact on the Achievement Motivation among the Guidance School Counselors in Algeria - حيدرة وحيدة; قيدوم أحمد (Journal of Education and Practice, 2018)
The objective of this study is to know the impact of the determinants of job satisfaction on the achievement motivation among the counselors of guidance and counseling school and vocational. In order to achieve the purposes of this study, the researchers adopted the descriptive analytical method ,we used two questionnaires: the first for the determinants of job satisfaction and the second one for measuring achievement motivation. The study was applied on a sample of (300) counselors had been selected in a random sample from vocational and school guidance centers of ten provinces.After confirming the psychometric properties of the measurement instruments and data processing by the statistical package for social sciences version20, the results show that the motivation of achievement can be predicted through the dimension of work content, but can not be predicted with other dimensions of job satisfaction of guidance counselors (self actualization, self esteem, achievement value, work conditions, promotion opportunities, carrier growth, work itself ).The research didn’t find a difference between achievement motivation and planning for the future, competition and perception of time due to the levels of job satisfaction, while there were statistically significant differences in the dimensions of the level of ambition, responsibility and perseverance.
Keywords: determinants of job satisfaction, achievement, motivation, work content, competition